Detecção de áreas degradadas no Município de Mata Grande (AL) com uso de geotecnologias - Santos, José Marcos Alves dos (2016)
Reducing the biodiversity of an environment with activities aimed at animal husbandry, shifting agriculture and self-consumption, and the collection of firewood for domestic consumption and commercialization, leads to soil degradation, which may be through erosion or loss Of fertility. Man has been using this environment for centuries, bringing environmental impacts as a result of this action. This situation is due to the elimination of the total or partial vegetation cover, in association with the inadequate use of the soil, allied to the climatic conditions, with long periods of drought. This situation has been a common scenario in the semi-arid region of Northeast Brazil. Therefore, through these exposures, it was necessary to detect and map degraded areas in the municipality of Mata Grande-AL, using geotechnologies (Remote Sensing and Qgis), which in recent years have acquired a fundamental character for environmental research and monitoring, a Efficient collection and treatment of data and information on natural resources. Through the Normalized Difference Vegetation Index - the vegetative changes occurred in the municipality were evaluated, and an analysis and comparison of the vegetation cover in the soil between the periods of 2013 to 2016 with images of the days, 10/12/2013, 11/27/2014, 11/14/2015 and 01/01/2016. Human activities are either directly or indirectly, and adverse climatic conditions are the main degradation factors in the study area, which characterized in the analyzed images a high percentage of exposed soil and low vegetation cover.